Gender codes : why women are leaving computing - Misa, Thomas J. (Hoboken, N.J. : Wiley ; [Piscataway, NJ] : IEEE Computer Society, 2010)
Looks at the history of women and men in computing, detailing how the computing profession emerged and matured, and how the field became male coded. Women's experiences working in offices, education, libraries, programming, and government are examined for clues on how and where women succeeded and where they struggled.
Gender codes : defining the problem / Thomas J. Misa -- Computer science : the incredible shrinking woman / Caroline Clarke Hayes -- Masculinity and the machine man : gender in the history of data processing / Thomas Haigh -- A gendered job carousel : employment effects of computer automation / Corinna Schlombs -- Meritocracy and feminization in conflict : computerization in the British government / Marie Hicks -- Making programming masculine / Nathan Ensmenger -- Gender and computing in the push-button library / Greg Downey -- Cultural perceptions of computers in Norway 1980-2007 : from "anybody" via "male experts" to "everybody" / Hilde G. Corneliussen -- Constructing gender and technology in advertising images : feminine and masculine computer parts / Aristotle Tympas, Hara Konsta, Theodor Lekkas, and Serkan Karas -- The pleasure paradox : bridging the gap between popular images of computing and women's historical experiences / Janet Abbate -- Programming enterprise : women entrepreneurs in software and computer services / Jeffrey R. Yost -- Gender codes : lessons from history / Thomas J. Misa -- Gender codes : prospects for change / Caroline Clarke Hayes.
Includes bibliographical references (pages 275-296) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Women in computer science; Computer industry; Femmes en informatique; Informatique -- Industrie; BUSINESS & ECONOMICS -- Infrastructure; BUSINESS & ECONOMICS -- Corporate & Business History; Industry; Computer industry; Women in computer science; Informatik; Computerindustrie; Frau; Informatik -- Frau; Frau -- Informatik; Computer -- Frau; Frau -- Computer